2006
DOI: 10.1097/01.wnr.0000239957.53072.f0
|View full text |Cite
|
Sign up to set email alerts
|

Cortical sulci and bipolar disorder

Abstract: The width of cortical sulci in bipolar patients (n=19) and healthy controls (n=35) was examined using a novel automated technique involving magnetic resonance imaging. All sulci were wider for bipolar patients than for healthy controls. Bipolar-control differences were largest for the superior and intermediate frontal sulci, smallest for the occipital and cingulate sulci, and intermediate in magnitude for the other sulci (intraparietal, inferior frontal, and central sulci). The results were interpreted in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Additionally, an increasing body of work focusing on molecular biological substrates of bipolar disorder describes alterations in the expression of WM genes that control myelination and oligodendrocyte function . Furthermore, there is evidence for increases in CSF [as reflected by ventricular and sulcal enlargement ] and elevated proinflammatory markers in bipolar disorder . These converging lines of evidence could conceivably explain FA decreases in terms of altered myelination and increased diffusivity in the absence of significant axonal loss.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an increasing body of work focusing on molecular biological substrates of bipolar disorder describes alterations in the expression of WM genes that control myelination and oligodendrocyte function . Furthermore, there is evidence for increases in CSF [as reflected by ventricular and sulcal enlargement ] and elevated proinflammatory markers in bipolar disorder . These converging lines of evidence could conceivably explain FA decreases in terms of altered myelination and increased diffusivity in the absence of significant axonal loss.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the hypothesis that the brain AA cascade is disturbed in BD. The hypothesis is based on the observation that each of the four mood stabilizers approved for treating BD, when given chronically to rats, downregulate AA turnover in brain phospholipids and other markers of brain AA metabolism, and on evidence of neuroinflammation and excitotoxicity associated with disease progression in BD, including brain atrophy and cell loss, cognitive decline and symptom worsening (5, 4346), in BD.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that the width of cortical sulci expands linearly with aging from early adulthood to old age (Liu et al, 2010;Kochunov et al, 2005;Magnotta et al, 1999). Additionally, developmental abnormalities of cortical sulci in bipolar disorder were observed by examining the width of sulci (Coyle et al, 2006). A recent study also found that the average sulcal span in the frontal lobe was negatively associated with processing speed in 38 healthy elderly individuals (Kochunov et al, 2010).…”
Section: Introductionmentioning
confidence: 95%